2019
DOI: 10.1186/s13613-019-0521-z
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm thickening in cardiac surgery: a perioperative prospective ultrasound study

Abstract: Background Diaphragm paresis is common after cardiac surgery and may delay the weaning from the ventilator. Our objective was to evaluate diaphragm thickening during weaning and secondly the muscle thickness as a marker of myotrauma. Methods Patients undergoing elective cardiac surgery were prospectively included. Ultrasonic index of right hemidiaphragm thickening fraction (TF) was measured as a surrogate criterion of work of breathing. A TF < 20% was defined as a low d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
1
16
0
2
Order By: Relevance
“…Nevertheless, as expected, the co-existence of these two conditions was associated with a poor survival. The presence of diaphragm dysfunction in critically ill patients has been associated with poor short-term prognosis in some studies [11,13,14,28], but not in others [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as expected, the co-existence of these two conditions was associated with a poor survival. The presence of diaphragm dysfunction in critically ill patients has been associated with poor short-term prognosis in some studies [11,13,14,28], but not in others [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent study has suggested that diaphragm function is predominantly a key determinant for the outcome of the spontaneous breathing trial rather than the outcome of extubation. Secondly, diaphragm dysfunction has been associated with complications such as reintubation, tracheostomy and prolonged ventilation (2), and postoperative complications (8,9). It is also associated with ICU mortality (7).…”
Section: Diaphragm Dysfunction Is a Major Concernmentioning
confidence: 99%
“…It has been reported in the literature that the risk and mortality of multiple operations is significantly higher than that of the initial operation [4,5]. The doctors often use continuous extracorporeal circulation video-assisted tricuspid valvuloplasty surgical method to treat the patients who have severe tricuspid regurgitation after cardiac surgery without severe pleural adhesion [6,7].…”
Section: Introductionmentioning
confidence: 99%